Case Report: Wide-to-Narrow QRS Tachycardia in a 3-Month-Old Infant - Zhao, Liang; Yan, Song; Wang, Tao; Hua, Yimin; Zhou, Kaiyu (Frontiers in Cardiovascular Medicine, 2021)
Introduction: It is rare to find that wide QRS tachycardia automatically changes to narrow QRS tachycardia, and it is more difficult to clarify the mechanism. Case report：A 3-month-old infant with recurrent paroxysmal supraventricular tachycardia underwent transesophageal cardiac electrophysiological examination. The wide QRS tachycardia was induced by atrial RS2 stimulation, and it soon changed to narrow QRS tachycardia automatically. By the accurate measurement of esophageal lead, it was found that the electrocardiogram changes completely conform to Coumel law. The mechanism of wide and narrow QRS tachycardia was anterograde atrioventricular reentrant tachycardia with or without ipsilateral functional bundle branch block, and the accessory pathway was defined as left free wall concealed accessory pathway. Conclusion: Transesophageal cardiac electrophysiological examination can reveal some special electrophysiological phenomena, and its non-invasive nature is especially suitable for infants.